171k views
0 votes
What is the solution to the equation 6x + 2 = 9x-1

2 Answers

4 votes

Answer:

Answer:

1

Step-by-step explanation:

Step 1:

6x + 2 = 9x - 1

Step 2:

2 = 3x - 1

Step 3:

3 = 3x

Answer:

1 = x

User Batichico
by
5.3k points
5 votes

Answer:

1

Explanation:

Step 1:

6x + 2 = 9x - 1

Step 2:

2 = 3x - 1

Step 3:

3 = 3x

Answer:

1 = x

Hope This Helps :)

User Birone
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.